Editorial - Thomas Wilson (Information Research: An International Electronic Journal)
Having moved the journal from Lund University to the University of Borås, my colleagues there are now in the process of transferring the journal to a new server and designing a new format, with publication within OJS. Previously, we have used OJS only up to the copy-editing stage of the workflow, but in future the papers will also be published from within the system.